State Procurement Electronic System Efficiency in Georgia - Medzmariashvili, Tinatin (European Journal of Economics and Business Studies, 2018)
State procurement has significant strategic importance for Georgia, while it serves the rational expenditure of the state funds and the creation of a transparent competitive environment for the state and the business sector. In the last few years, the development of electronic technologies have formulated united state procurement electronic system. State financial resource spending requires business correspondence based on a single electronic system, which facilitates the acquisition of the buyer and the supplier openly, easily and without any unnecessary restrictions. Electronic system elaboration ensures maximal transparency of procurement procedures and rational spending of the state financial resources. Furthermore, increases competition among the bidders participating in the tender and raises public awareness. E-procurement system increases efficiency of the procurement processes, through saving purchaser’s and potential supplier’s financial, human and time-consuming resources. Besides, the tender procedures are transparent and easy to understand for any person interested in it.It is effective and efficient for any country to use the state procurement electronic system, as it provides transparent procedures and eliminates competition restrictions, corruption and discrimination risks.